Long-term editing of brain circuits using an engineered electrical synapse - Elizabeth Ransey; Gwenaëlle E. Thomas; Elias M. Wisdom; Agustin Almoril-Porras; Ryan Bowman; Elise Adamson; Kathryn K. Walder-Christensen; Jesse A. White; Dalton N. Hughes; Hannah Schwennesen; Caly Ferguson; Kay M. Tye; et al. (Nature, 2026)
Abstract Electrical signalling across distinct populations of brain cells underpins cognitive and emotional function. However, approaches that selectively regulate electrical signalling between two cellular components of a mammalian neural circuit remain sparse. Here we engineered an electrical synapse composed of two connexin proteins 1 found in Morone americana (white perch fish)—connexin 34.7 and connexin 35—to accomplish mammalian circuit modulation. By exploiting protein mutagenesis, devising a new in vitro system for assaying connexin hemichannel docking, and performing computational modelling of hemichannel interactions, we uncovered a structural motif that contributes to electrical synapse formation. Targeting this motif, we designed connexin 34.7 and connexin 35 hemichannels that dock with each other to form an electrical synapse but not with other major connexins expressed in the mammalian central nervous system. We validated this electrical synapse in vivo using worms ( Caenorhabditis elegans ) and mice ( Mus musculus ). We demonstrate that it can strengthen communication across neural circuits composed of pairs of distinct cell types and modify behaviour accordingly. Thus, we establish ‘long-term integration of circuits using connexins’ (LinCx) for precision circuit editing in mammals.